2005
DOI: 10.1103/physreve.71.016401
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal-thermal-equilibrium model of a pulsed capillary discharge waveguide

Abstract: Slow pulsed capillary discharges are under investigation for use as plasma channel waveguides in laser-wakefield acceleration. In this study, we present a non-local thermal equilibrium (non-LTE) plasma model with a model for the wall temperature coupled to it. This model is used to describe an example of a slow pulsed capillary discharge, and the results are compared with experimental results. The agreement is satisfactory, indicating suitability of our model. Significant deviations from LTE are found during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 24 publications
4
83
0
Order By: Relevance
“…The latter model has been discussed in great detail in Ref. 27. It has been validated by comparison with an experiment, 27 used for parameter studies, 27,31 and a slightly modified version has been used to investigate the effect of modulation of the capillary radius.…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter model has been discussed in great detail in Ref. 27. It has been validated by comparison with an experiment, 27 used for parameter studies, 27,31 and a slightly modified version has been used to investigate the effect of modulation of the capillary radius.…”
Section: The Modelmentioning
confidence: 99%
“…27. It has been validated by comparison with an experiment, 27 used for parameter studies, 27,31 and a slightly modified version has been used to investigate the effect of modulation of the capillary radius. 32 We will restrict the discussion of the model used in this work to a summary, emphasizing the difference between the present model and the model used for earlier studies, and refer the interested reader to Ref.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen gas, introduced through holes near the capillary ends, was ionized by striking a discharge between electrodes located at each end of the capillary. Measurements [129] and modeling [189,190] showed that a fully ionized, approximately parabolic channel was formed. Hydrogen gas was introduced into the capillary waveguide using two gas slots in the 190 µm and 225 µm diameter capillary and three in the 310 µm capillary.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogen gas, introduced through holes near the capillary ends, was ionized by striking a discharge between electrodes at the capillary ends. Measurements [8] and modelling [10], [11] showed that a fully-ionized, approximately parabolic (with density minimum on axis) plasma channel is formed.…”
Section: Channel-guided Laser Wakefield Acceleratormentioning
confidence: 99%